PENANAMAN NILAI-NILAI PANCASILA DENGAN MEDIA KOMIK PANCASILA (KOPALA) DI PESANTREN YATIM CAHAYA MADINAH TANGERANG - Dyana Ayundasari; Aulia Rahmah; Dedek Putra Bungsu; Feri Agustiawan; Pety Tanjung Sari; Chandra Fitra Arifianto (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
Today is the understanding of the values ​​of Pancasila in the younger generation is getting eroded. Of course, it is hoped that this will not happen to young santri. With a solid Islamic background, santri find it easier to understand the values ​​of Pancasila and do not fall into a negative understanding of Pancasila. Therefore, this community service activity aims to provide a new understanding of the use of visual media in the form of the Pancasila Comic (abbreviated as KOPALA). In realizing this goal, the methods used are lectures and evaluation using games by utilizing devices that can display comic visuals. At the same time, the participants who were included in this activity were the santri, who were also students at the Madrasah Ibtidaiyah and Madrasah Tsanawiyah benches, totalling 17 santri. They are santri of Pesantren Yatim Cahaya Madinah in South Tangerang. In general, the implementation of the activities was successful although with some shortcomings, such as facilities. Furthermore, it is necessary to apply the same action to adolescents at the Madrasah Aliyah level and training for teachers in literacy, software and hardware, gadgets, and classroom management